Use of contraception and knowledge of health technologies - Robles Soto, Arodys (1997)
Are the behavioral aspects of use of family planning and primary health care services linked? The question addresses a key assumption in the rationale of reproductive health programs. In this paper we address the basic hypothesis underlying this assumption: that women who use contraceptives are more likely to have knowledge of health technologies to improve child survival. They would also be more amenable to use available health services or seek the necessary health technologies to treat their child. The study seeks to elucidate the relationship between knowledge and use of contraception and knowledge and use of health technologies. The analysis looks at the determinants of knowledge and the relationship between knowledge and use of health technologies. Both, use of contraception and improvement of child health involve a behavioral change. Adoption of contraception implies a conscious decision to modify behavior in order to attain a desired pattern of family formation. Changes in behavior however are contingent upon knowledge about the effective means of controlling fertility (Coale, 1973). Similarly, changes in child survival also entail a series of behavioral changes. Decline of child mortality in developed countries at the beginning of the century was associated with changes in personal health behavior (Preston and Haines, 1991; Ewbank and Preston, 1990). These changes came about when the knowledge base of disease causation enabled individuals to modify behavior in order to attain better health. Considerable resources are spent today in the promotion of health technologies such as immunization and use of oral re hydration therapy (ORT). While vertical interventions have been adopted because of their simplicity, their impact on child survival ultimately depends on the ability of the mother to use them effectively. A mother needs to know the immunization schedule the child requires and the proper way of using oral rehydration packets. But most important, a mother first has to understand the benefits of using these technologies and be able to acquire them at the appropriate time. Consequently, an integral part of both family planning programs and primary health care programs is the dissemination of information on contraception and child care that will result in better health of mothers and children.